2008
DOI: 10.1243/09544070jauto493
|View full text |Cite
|
Sign up to set email alerts
|

Diesel engine variable-geometry turbine turbocharger controlled by a multi-agent-based algorithm

Abstract: This paper provides an innovative technique for the control of a variable-geometry turbine in a turbocharged compression ignition engine. Such a control algorithm is based on a multi-agent System scheme. It is seldom that agents are considered as stand-alone systems; on the contrary, their main strength can be found in the interaction with other agents, constituting the so-called multi-agent System. An agent is a software or hardware entity that can receive signals from the environment and act upon that enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The operation of a variable geometry turbocharger (VGT) is a function of the engine speed and load with the developments in recent years focusing on emission reduction strategies. 14 Thus, at fixed engine speed and load, the optimal turbine inlet geometry is fixed. However, in an internal combustion engine, the pulsating nature of the exhaust flow means that the flow conditions at the turbine inlet are changing continuously regardless of the engine speed and load.…”
Section: Introductionmentioning
confidence: 99%
“…The operation of a variable geometry turbocharger (VGT) is a function of the engine speed and load with the developments in recent years focusing on emission reduction strategies. 14 Thus, at fixed engine speed and load, the optimal turbine inlet geometry is fixed. However, in an internal combustion engine, the pulsating nature of the exhaust flow means that the flow conditions at the turbine inlet are changing continuously regardless of the engine speed and load.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the current PID embedded strategy developed by BOSCH, a significant improvement in desired set-points tracking was obtained. Mastrovito et al (22) used a multi-agent system (MAS) approach to manage the boost control process of a modern turbocharged diesel engine. The MAS controller performed better than the traditional PID controller in terms of promptness but also showed a good level of adaptivity, precision, robustness and stability.…”
Section: Figszipmentioning
confidence: 99%
“…4 Over the past few years, VGT control methods and strategies have undergone rapid development. Mastrovito et al 6 proposed an innovative technique for VGT control based on a multi-agent system, using a fuzzy logic system to represent the agents' internal structure. It indicated that this control technique takes into account the nonlinearity of the system.…”
Section: Introductionmentioning
confidence: 99%